Revenge In Oliver Bowden's Assassin's Creed: Renaissance Novel (2009): A Psychoanalytic Approach - Abdalla, Ahmad Rifqi, Drs. Abdillah Nugroho, M. Hum, Siti Fatimah, S. Pd, M. Hum (2014)
This research is proposed to analyze how the revenge is reflected in Ezio Auditore as the major character in Oliver Bowden's Assassin's Creed: Renaissance novel based on the structural element and psychoanalytic approach. The type of this research is qualitative research. This study focuses on the major character of the novel. This study uses two data source, primary and secondary data source. The primary data source is the novel itself and the secondary data source is the information related with the study. The method of collecting data is qualitative method. Based on the analysis, the researcher draws two onclusions: first, based on the structural analysis of the novel, the structural element of the novel is related each other to build a good unity and cannot be separated. Second, based on the psychoanalytic analysis, the research shows that the problem faced by the major character leads him to seek for revenge and look for resolution of his problem.